PENGARUH SISTEM INFORMASI AKUNTANSI, GAYA KEPEMIMPINAN DAN KOMPLEKSITAS TUGAS TERHADAP KINERJA KARYAWAN - Siti Nurlaela, Eny Parjanti, Kartika Hendra Titisari dan (Paradigma, 2014)
This study aims to examine and analyze the effect of the accounting information systems, and the complexity ofthe task of leadership style on employee performance. The populationin this study is the employees who work in the field of retail technology company in the city of Surakarta. The number of respondents in this study were 56 respondents from 90 the number of questionnaires distributed. The methods used in this study is the purposive sampling. The method of data analysis use dismultiple linear regression analysis and processed using SPSS17. The results showed hat the accounting information systems, leadership styleandtask complexity and significant influence on employee performance..The coefficient of determination (R2) of 0.315 which shows that 31.5% of employee performance variables can be explained by the  independent variables accounting information systems, leadership styles and the complexity of the task, while the remaining68.5% is explained by other variables.   Keywords: accounting information systems, leadership styles, the complexity of the task, the  performance of employees, information technology